The extra costs of having a disability: the case of IIUM - Mohd Amin, Ruzita; Md Adros, Nur Syuhada (IIUM Press, International Islamic University Malaysia, 2019)
The information on extra costs of disability among developing countries, including Malaysia, is lacking and the issue seems neglected. As a result, an appropriate amount of monetary assistance that should be provided to the disabled community in Malaysia could not be determined. This paper undertakes a preliminary analysis of the extra costs of having a disability, by taking the staff of International Islamic University Malaysia (IIUM) as the sample as to calculate the extra costs of having a disability. The standard of living approach is adopted, and the extra costs are calculated by dividing the estimated coefficient of disability variables by the estimated coefficient of income. This paper analyses the extra costs among households containing one person with disabilities, and also across different severity levels, types of disability, according to gender, and residential area (i.e. urban or rural). Overall, a household containing one person with disabilities accounted 27.5 per cent out of their monthly income to fulfil disability-related needs.